ChemInform Abstract: Organo Phosphorus—Selenium Heterocycles Derived from Haloalkanols and Alkenes. Issue 7 (22nd February 2013) - Hua, Guoxiong; Fuller, Amy L.; Slawin, Alexandra M. Z.; Woollins, J. Derek
Abstract Five‐ or six‐membered heterocycles are synthesized by treatment of bromoalkanones or alkenes with Woollin′s reagent (I).